2009
DOI: 10.1093/cercor/bhp154
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Variation in Expression of the Candidate Dyslexia Susceptibility Gene Homolog Kiaa0319 on Neuronal Migration and Dendritic Morphology in the Rat

Abstract: We investigated the postnatal effects of embryonic knockdown and overexpression of the candidate dyslexia gene homolog Kiaa0319. We used in utero electroporation to transfect cells in E15/16 rat neocortical ventricular zone with either 1) small hairpin RNA (shRNA) vectors targeting Kiaa0319, 2) a KIAA0319 expression construct, 3) Kiaa0319 shRNA along with KIAA0319 expression construct ("rescue"), or 4) a scrambled version of Kiaa0319 shRNA. Knockdown, but not overexpression, of Kiaa0319 resulted in periventric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
102
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(119 citation statements)
references
References 56 publications
15
102
2
Order By: Relevance
“…Study of the most replicated linkage region, the 6p22 region, suggested the implication of two other genes, i.e., DCDC2 and KIAA0319 (Meng et al 2005;Cope et al 2005;Schumacher et al 2006). Most of these putative genes contribute to neuron migration (Pechansky et al 2010;Massinen et al 2011;Currier et al 2011), consistent with anatomical studies that show structural cortical anomalies in dyslexic individuals (Galaburda et al 1985). Association studies have revealed correlations with genetic variants, but results concerning specific risk factors remain mainly sparse or inconsistent in the different samples (for review Scerri and Schulte-Körne 2010).…”
supporting
confidence: 68%
“…Study of the most replicated linkage region, the 6p22 region, suggested the implication of two other genes, i.e., DCDC2 and KIAA0319 (Meng et al 2005;Cope et al 2005;Schumacher et al 2006). Most of these putative genes contribute to neuron migration (Pechansky et al 2010;Massinen et al 2011;Currier et al 2011), consistent with anatomical studies that show structural cortical anomalies in dyslexic individuals (Galaburda et al 1985). Association studies have revealed correlations with genetic variants, but results concerning specific risk factors remain mainly sparse or inconsistent in the different samples (for review Scerri and Schulte-Körne 2010).…”
supporting
confidence: 68%
“…An increasing number of studies have investigated the function of RD risk genes in animal models [2][3][4][5][6][7][8][9][10][11][12][13], and the neurobiological and behavioral consequences of genetic RD risk variants in humans [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31], motivating the need for a synthesis of these findings, especially because they relate to emerging avenues of human research on the role of neurochemistry [32] and neural oscillations [33][34][35][36] in RD. Here, we present a timely integration of diverse lines of current research linking some of the key neural and behavioral deficits associated with RD to basic neural processes.…”
Section: Premise Of the Neural Noise Hypothesismentioning
confidence: 99%
“…Processes in light text are not discussed in detail in the main text. Numbers by arrows refer to supporting references in the main text ( [5,9,10,11,27,39,44,45,49,55,58,72,75,80,82,84,85,86,88,89,90]). In a balanced excitation-inhibition regimen, stimuli evoke excitatory synaptic conductances (green curve) followed by comparable inhibitory conductances (red curve) within a few milliseconds.…”
Section: Key Figurementioning
confidence: 99%
“…75 Recently, embryonic knockdown of Kiaa0319 in rats was found to result in significant arrest of neuronal migration and subsequently causes specific types of neuronal migration anomalies in the postnatal rat brain whereas, in contrast, embryonic overexpression of Kiaa0319 does not cause gross neuronal migration anomalies. 83 Lastly, apart from a main variant (variant A) of KIAA0319, two alternatively spliced products of the gene exist (variants B and C), which encode KIAA0319 isoforms that lack a transmembrane domain. Isoform B was found to be secreted, suggesting that KIAA0319 could be involved not only in cell-cell interactions, but also in extracellular signaling.…”
mentioning
confidence: 99%